First report of the North Atlantic myrionematoid brown alga Ulonema rhizophorum Foslie (Phaeophyceae, Chordariaceae) in the Mediterranean Sea - TASKIN, E. (Mediterranean Marine Science, 2013)
The myrionematoid brown alga Ulonema rhizophorum Foslie (Phaeophyceae, Chordariaceae) is reported for the first time from the Mediterranean Sea. This species was collected growing as an epiphyte on Ulva sp. from the Dardanelles (Sea of Marmara, Turkey) in the midlittoral zone. Ulonema rhizophorum is characterized by downwardly produced rhizoids from the basal system. A key to the Mediterranean related genera of Ulonema is provided.